2010
DOI: 10.5539/jas.v2n2p181
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation of Nerium Oleander through the Immature Pods

Abstract: Oleander (Nerium oleander L.) is a vegetatively propagated ornamental plant valued for its evergreen foliage and showy terminal flower clusters that are available in different colours. Oleander is cultivated recently as a flowering pot plant and therefore abundant propagation plant material for commercial use is of great importance. This species also produces secondary metabolites (Paper & Franz 1989), some of which are of pharmacological interest. In vitro culture of plants has gained importance during recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…In the present study, the germination percentage of N. oleander zygotic embryos was found much higher than the wild mature seeds in the culture medium, which might be due to the presence of various inhibitors in the seed coat (Kaveri & Rao, 2015). However, some other direct (Karrunakaran & Shri, 2010;Hatzilazarou et al, 2019) and indirect in vitro micropropagation techniques are reported from this plant (DH Paper, 1989;Santos et al, 1994;Vila et al, 2010) yet no ZEC and CGs profiling of acclimatized and in vitro raised plants found to be reported in our knowledge. ZEC depends on many factors including the source of carbon and other nutrients used, which helps in the germination, survival and growth of the delicate IVP.…”
Section: Discussioncontrasting
confidence: 63%
“…In the present study, the germination percentage of N. oleander zygotic embryos was found much higher than the wild mature seeds in the culture medium, which might be due to the presence of various inhibitors in the seed coat (Kaveri & Rao, 2015). However, some other direct (Karrunakaran & Shri, 2010;Hatzilazarou et al, 2019) and indirect in vitro micropropagation techniques are reported from this plant (DH Paper, 1989;Santos et al, 1994;Vila et al, 2010) yet no ZEC and CGs profiling of acclimatized and in vitro raised plants found to be reported in our knowledge. ZEC depends on many factors including the source of carbon and other nutrients used, which helps in the germination, survival and growth of the delicate IVP.…”
Section: Discussioncontrasting
confidence: 63%
“…In Asian country and therefore the tropics it grows naturally in wet soil, shallow water and marches. The herb can be found at elevations from sea level to altitudes of 4,400 feet and is easily cultivated if adequate water available (Soundararajan et al, 2011). It has a great market demand due to its high medicinal uses.…”
mentioning
confidence: 99%
“…Somaclonal variation is defined as genetic and phenotypic variation among clonally propagated plants of a single donor clone (Larkin, 1987). According to recent reports, somaclonal variations were detected among micropropagated plantlets in many taxa at levels such as phenotypic and cytological (Podwyszyńska, 2005;Zayova et al, 2010), biochemical and molecular (Soundararajan and Karrunakaran, 2010;Kanungo et al, 2012;Senapati et al, 2012;Saha et al, 2012).…”
Section: Introductionmentioning
confidence: 99%